Les tiers-lieux en France, laboratoires de nouvelles solidarités socio-spatiales ? - Marie Dagonneau (Bulletin de l’Association de Géographes Français)
Sometimes understood as a community psycho-socio-anthropological process born of the discrepancy between societal needs and management of these by the institution (in the broad sense), the third place is experiencing a lively societal topicality on the fringes of the dominant system and at the light of the contributions of digital culture. It experiments and disseminates, on a territorial scale and in various formal guises, the utopia of the culture of the commons, thus becoming one of the privileged levers of a model of solidarity, citizen, endogenous and empirical development of the territories. To this extent, it proves to be a key to reading and a catalyst for new uses and representations of rural and urban territories.